Enhanced Photocatalytic Hydrogen Evolution by TiO2: A Synergistic Approach with Defect-Rich SnS2 and Ti3C2 MXene Cocatalysts - Saminathan Varadarajan; Andiappan Kavitha; Periasamy Selvaraju; Sankaran Esakki Muthu; Krishnamoorthy Gurushankar; Sengottaiyan Shanmugan; Karthik Kannan (Hydrogen, 2024)
Enhanced photo-induced electron utilization leads to efficient photocatalytic hydrogen production. The inefficient separation of photo-induced electron–hole pairs has hindered this process. This study introduces a synergistic approach using defect-rich SnS2 and Ti3C2 MXene as cocatalysts in a two-step hydrothermal process to address this challenge. By integrating these materials with TiO2 nanosheets, we create a novel composite, SnS2/Ti3C2/TiO2 (STT), that significantly boosts photocatalytic hydrogen evolution. The defect-rich SnS2 provides abundant active sites for hydrogen generation, while Ti3C2 MXene facilitates photo-induced charge separation. The synergistic combination of charge carrier diffusion enhances chromophore absorption, thereby increasing the overall photocatalytic hydrogen-production rate, achieving several grams of hydrogen per hour per gram of double cocatalysts with molybdenum vacancies. Characterization techniques confirm the phase composition of the composite (STT). Compared to pristine TiO2 and other composites, the STT composite, optimized with a 150 °C hydrothermal treatment, shows a photocatalytic H2-production rate nearly 192 times higher than that of pure TiO2 and 6 times higher than that of other composites. The presence of molybdenum vacancies in SnS2 further enhances its specific activity for hydrogen evolution by suppressing carrier recombination and providing additional active sites. Moreover, Ti3C2 MXene and SnS2 act as dual cocatalysts, improving electronic conductivity and electron-transfer efficiency. Our findings demonstrate the potential of combining defect-rich SnS2 and Ti3C2 MXene to develop highly efficient and sustainable photocatalysts for hydrogen production. TiO2 has been in situ grown on highly conductive Ti3C2 MXene, and SnS2, rich in molybdenum vacancies, is uniformly distributed on the TiO2/Ti3C2 composite through the two-step hydrothermal method. The presence of molybdenum vacancies in SnS2 further enhances its specific activity for hydrogen evolution by suppressing carrier recombination and providing additional active sites. Moreover, Ti3C2 MXene and SnS2 act as dual cocatalysts, improving electronic conductivity and electron-transfer efficiency. Our findings demonstrate the potential of combining defect-rich SnS2 and Ti3C2 MXene to develop highly efficient and sustainable photocatalysts for hydrogen production.